Combating the Covid-19 Hate and Racism Speech on Social Media - Al-Jarf, Reima (Technium Social Sciences Journal, 2021)
The spread of Covid-19 worldwide has been associated with hate and racism speech on social media which sometimes encourages violence and bullying in the different communities. Some officials, public figures and even common people, including students, have been expressing hate, racism, negative, hostile, and intolerant attitudes towards certain groups of people based on their color, origin, race, religion or social/political stance. This study surveys students and instructors’ views of Covid-19 five months after the outbreak of the pandemic, and whether they consider it a punishment from God to certain countries or not. Based on the findings, it proposes the creation of an anti-hate Twitter page to teach students tolerance rather than negative sentiment associated with Covid-19.